Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1039/c3dt50875g
|View full text |Cite
|
Sign up to set email alerts
|

Precision synthesis of silicon nanowires with crystalline core and amorphous shell

Abstract: A synthetic route to crystalline silicon (Si) nanowires with an amorphous Si shell is reported. Trisilane (Si 3 H 8 ) and Sn(HMDS) 2 are decomposed in supercritical toluene at 450°C. Sn(HMDS) 2 creates Sn nanoparticles that seed Si nanowire growth by the supercritical fluid-liquid-solid (SFLS) mechanism. The Si : Sn ratio in the reaction determines the growth of amorphous Si shell. No amorphous shell forms at relatively low Si : Sn ratios of 20 : 1, whereas higher Si : Sn ratio of 40 : 1 leads to significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…1D, Table 1). This shell could for example consist of a poly-phenylsilane organic layer as previously described by Chan et al, 49 or of amorphous silicon as observed by Bogart et al 50 To gain further insight into the surface state of the obtained SiNWs, additional analyses were carried out. First, the amount of oxygen in SiNWs was estimated by EDX (Table S1 †).…”
Section: Resultsmentioning
confidence: 99%
“…1D, Table 1). This shell could for example consist of a poly-phenylsilane organic layer as previously described by Chan et al, 49 or of amorphous silicon as observed by Bogart et al 50 To gain further insight into the surface state of the obtained SiNWs, additional analyses were carried out. First, the amount of oxygen in SiNWs was estimated by EDX (Table S1 †).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, solution-based growth methods have been examined as more cost-effective alternatives that allow the formation of Si NWs at higher yields than typically afforded by CVD processes [232][233][234][235][236]. These reports also highlight the negative impact of Au as a catalyst material for LIB applications and proposed the use of either Sn [233,236] or In [237] as electrochemically active catalyst materials, which led to improved performance compared to Au-containing electrodes.…”
Section: Methods Of Fabricating Si Nws: Vapor-liquidsolid Growthmentioning
confidence: 94%
“…Interestingly, a significant amount of twin defects (a type of grain boundary) were observed in the NWs (Figure 2 (b,c)), which were also seen in NWs synthesised by trisilane as a reactant for SFLS growth of Si NWs. 42,43 Twin defects are considered to be formed in parallel to the crystal growth axis of the NW and are indicated by the micro-faceting appearance. 44 Effectively, they change the crystallographic orientation of the NW such as crystal-bonding disorders.…”
Section: Eq 2 ( ) = +mentioning
confidence: 99%